Attitudes toward dementia screening and influential factors in older adults in China. Issue 2 (1st December 2022) - Xue, Bing; Luo, Chang; Luo, Xianwu
Abstract: Background: Dementia will likely be an ongoing concern for future generations, and according to the World Health Organization, two‐thirds of dementia cases are missed diagnoses. We aimed to explore the attitudes of older adults toward dementia screening and the related influencing factors. Methods: A multicentre cross‐sectional study was conducted. Data were collected using questionnaires between 2020 December and 2021 June from five provinces in China. The study included older adults aged 60 years or older, living in China. A sociodemographic questionnaire and the Perceptions Regarding Investigational Screening for Memory in Primary Care scale were used to assess attitudes toward and influencing factors of dementia screening. Results: A total of 279 participants completed the questionnaires. The results revealed housing status as a positive factor in the acceptance dimension, while high income was the primary positive factor in the benefits of screening dimension. Having religious beliefs, low income, and never participating in social activities were positive factors for the stigma dimension. Widowed marital status and participation in social activities were negative factors for the independence dimension, while having religious beliefs positively influenced the suffering dimension. Conclusions: This study showed that participants held a relatively positive attitude toward dementia screening, although they had concerns about stigma and negative impact on independence. Further studies are required to develop intervention strategies to help older adults improve their attitudes and quality of life, promote cognitive health, and facilitate healthy ageing.